Differential Activities of Antioxidant Enzymes, Superoxide Dismutase, Peroxidase, and Catalase vis-à-vis Phosphine Resistance in Field Populations of Lesser Grain Borer (Rhyzopertha dominica) from India - Hagalavadi Vijaykumar Ranjith; Doddachowdappa Sagar; Vinay Kumari Kalia; Anil Dahuja; Sabtharishi Subramanian (MDPI AG, 2023)
Susceptibility to phosphine was compared in 15 populations of lesser grain borer (Rhyzopertha dominica) collected from grain storage godowns across India. A high level of resistance to phosphine was noticed in R. dominica collected from northern India compared to those collected from northeastern regions of India. The median lethal concentration values varied from 0.024 mg/L to 1.991 mg/L, with 1.63 to 82.96-fold resistance compared to laboratory susceptible checks. Antioxidant enzymes have been reported to negate the reactive oxygen species generated upon encountering the fumigant phosphine. Distinct differences in the activity of antioxidant enzymes were noticed in the field populations exposed to phosphine. Peroxidase activity varied between 1.28 and 336.8 nmol H2O2 reduced/min/mg protein. The superoxide dismutase inhibition rate was between 81.29 and 99.66%, and catalase activity varied between 6.28 and 320.13 nmol H2O2 reduced/min/mg protein. The findings of our investigation show that the activities of peroxidase and superoxide dismutase are positively linked (p < 0.01) with an increase in resistance ratios, whereas catalase was found to have a negative association with resistance to phosphine. The reported results elucidate the differential activities of principal antioxidant enzymes in scavenging the oxyradicals (O2•−, H2O2,•OH) associated with tolerance to phosphine in R. dominica.